Proposing an Expanded Measure for Comparing Online/Hybrid to Face-to-face Courses (Journal of Education and Development, 2018)
Online education continues to increase. With increased online offerings, it is important to evaluate the integrity or equivalence of online/hybrid courses relative to face-to-face (F2F) courses. This study used three separate samples of business undergraduates taking both online/hybrid and F2F courses in the same semester (i.e., mixed course delivery format), across summer, fall and spring semesters. Eight items were used to assess students’ perceived favorability of online courses (PFoOC) compared to F2F courses. Across all three samples, two related but distinct sources for course comparison consistently emerged, instructor-related and peer related. An eight-item measure represents a necessary improvement over a previously developed four-item PFoOC measure, because it allows for additional relevant item comparisons between online/hybrid versus F2F courses. It is hoped that this measure can be used to further research evaluating online education.